0

I would like to put the following equations in the left side of my text, I do not know which command will be useful for that. I used align, but it put all equations in right most side of paper. More precisely, I want to put all of the equations below each other and their position be the left side of paper.

\begin{document}
\begin{align*}
(f,f)_{[x^3]_{1}}  = (f,f)_{[x^3]_{1}}=0 \\
    (f,g)_{[x^3]_{1}} =(f,g)_{[x^3]_{3}}=0\\
    (f,h)_{[xxy]_{1}}=(f,h)_{[xxy]_{3}}=0\\
    (f,p)_{[xxy]_{1}}=(f,p)_{[xxy]_{3}}=0\\
    (f,m)_{[xxt]_{1}}=[xx]_{1} \dashv t  - x \dashv ([xt]_{1} - [tx]_{2})= [xtx]_{1}\\
    (f,m)_{[xxt]_{3}}=[xx]_{1}\vdash t - x \vdash ([xt]_{1} - [tx]_{2})=[xxt]_3-[xxt]_2+[xtx]_3\\
    (g,f)_{[x^3]_{1}}=(g,f)_{[x^3]_{3}}=0\\
\end{align*}
\end{document}
2
  • you have used align but marked no alignment points (should be &=) but we can not run the code to see any problems as you only posted a fragment and you ask about text but the fragment has no text, if you want equations on the left, is it a two column document? Please edit your question Commented Aug 12, 2019 at 18:23
  • You have to add an ampersand in each row in front of each alignment point (for instance, in front of the first = sign in each row). If you don't, it will be aligned by the end of each row.
    – Bernard
    Commented Aug 12, 2019 at 18:24

3 Answers 3

1

The package nncmath provide environment fleqn which push equation to the left text border:

\documentclass{article}
\usepackage{nccmath}

%---------------- show page layout. don't use in a real document!
\usepackage{showframe}
\renewcommand\ShowFrameLinethickness{0.15pt}
\renewcommand*\ShowFrameColor{\color{red}}
%---------------------------------------------------------------%

\begin{document}

\begin{fleqn}
    \begin{gather*}
(f,f)_{[x^3]_{1}}  = (f,f)_{[x^3]_{1}}=0 \\
(f,g)_{[x^3]_{1}} =(f,g)_{[x^3]_{3}}=0 \\
(f,h)_{[xxy]_{1}}=(f,h)_{[xxy]_{3}}=0 \\
(f,p)_{[xxy]_{1}}=(f,p)_{[xxy]_{3}}=0 \\
(f,m)_{[xxt]_{1}}=[xx]_{1} \dashv t  - x \dashv ([xt]_{1} - [tx]_{2})= [xtx]_{1}\\
(f,m)_{[xxt]_{3}}=[xx]_{1}\vdash t - x \vdash ([xt]_{1} - [tx]_{2})=[xxt]_3-[xxt]_2+[xtx]_3\\
(g,f)_{[x^3]_{1}}=(g,f)_{[x^3]_{3}}=0\\
    \end{gather*}
\end{fleqn}

\end{document}

enter image description here

(red lines indicate text borders)

1

Here is a possible suggestion including three different alignments (red lines indicate margins):

enter image description here

\documentclass{article}
\usepackage{amsmath}


\begin{document}
\begin{flalign*}
(f,f)_{[x^3]_{1}}  &= (f,f)_{[x^3]_{1}}=0 &&\\ 
    (f,g)_{[x^3]_{1}} &=(f,g)_{[x^3]_{3}}=0 \\
    (f,h)_{[xxy]_{1}}&=(f,h)_{[xxy]_{3}}=0 \\
    (f,p)_{[xxy]_{1}}&=(f,p)_{[xxy]_{3}}=0 \\
    (f,m)_{[xxt]_{1}}&=[xx]_{1} \dashv t  - x \dashv ([xt]_{1} - [tx]_{2})= [xtx]_{1}\\
    (f,m)_{[xxt]_{3}}&=[xx]_{1}\vdash t - x \vdash ([xt]_{1} - [tx]_{2})=[xxt]_3-[xxt]_2+[xtx]_3\\
    (g,f)_{[x^3]_{1}}&=(g,f)_{[x^3]_{3}}=0\\
\end{flalign*}

\begin{align*}
(f,f)_{[x^3]_{1}}  &= (f,f)_{[x^3]_{1}}=0 \\ 
    (f,g)_{[x^3]_{1}} &=(f,g)_{[x^3]_{3}}=0 \\
    (f,h)_{[xxy]_{1}}&=(f,h)_{[xxy]_{3}}=0 \\
    (f,p)_{[xxy]_{1}}&=(f,p)_{[xxy]_{3}}=0 \\
    (f,m)_{[xxt]_{1}}&=[xx]_{1} \dashv t  - x \dashv ([xt]_{1} - [tx]_{2})= [xtx]_{1}\\
    (f,m)_{[xxt]_{3}}&=[xx]_{1}\vdash t - x \vdash ([xt]_{1} - [tx]_{2})=[xxt]_3-[xxt]_2+[xtx]_3\\
    (g,f)_{[x^3]_{1}}&=(g,f)_{[x^3]_{3}}=0\\
\end{align*}

\begin{flalign*}
    &(f,f)_{[x^3]_{1}}  = (f,f)_{[x^3]_{1}}=0 &&\\ 
    &(f,g)_{[x^3]_{1}} =(f,g)_{[x^3]_{3}}=0 \\
    &(f,h)_{[xxy]_{1}}=(f,h)_{[xxy]_{3}}=0 \\
    &(f,p)_{[xxy]_{1}}=(f,p)_{[xxy]_{3}}=0 \\
    &(f,m)_{[xxt]_{1}}=[xx]_{1} \dashv t  - x \dashv ([xt]_{1} - [tx]_{2})= [xtx]_{1}\\
    &(f,m)_{[xxt]_{3}}=[xx]_{1}\vdash t - x \vdash ([xt]_{1} - [tx]_{2})=[xxt]_3-[xxt]_2+[xtx]_3\\
    &(g,f)_{[x^3]_{1}}=(g,f)_{[x^3]_{3}}=0\\
\end{flalign*}

\end{document}
2
  • It solved my question, but the only problem is that in the margin, all $(f,f)$ are not written below each other completely and there exists small distances from red margin
    – user118746
    Commented Aug 12, 2019 at 18:33
  • @user118746: I have added a third variant.
    – leandriis
    Commented Aug 12, 2019 at 18:40
0

Just to add a little variant in which some equations are centered and others are aligned to the left, of course is not as elegant as @leandriis answer but it could be useful:

\documentclass{article}
\usepackage{amsmath}
\usepackage{blindtext}

\begin{document}

\begin{align*}
    & (f,f)_{[x^3]_{1}} = (f,f)_{[x^3]_{1}}=0 \\ 
    & (f,g)_{[x^3]_{1}} = (f,g)_{[x^3]_{3}}=0 \\
    & (f,h)_{[xxy]_{1}} = (f,h)_{[xxy]_{3}}=0 \\
    & (f,p)_{[xxy]_{1}} = (f,p)_{[xxy]_{3}}=0 \\
    & (f,m)_{[xxt]_{1}} = [xx]_{1} \dashv t  - x \dashv ([xt]_{1} - [tx]_{2}) = [xtx]_{1}\\
    & (f,m)_{[xxt]_{3}} = [xx]_{1}\vdash t - x \vdash ([xt]_{1} - [tx]_{2})=[xxt]_3-[xxt]_2+[xtx]_3\\
    & (g,f)_{[x^3]_{1}} =(g,f)_{[x^3]_{3}}=0\\
\end{align*}

%some blind text to check that margins are correct
\blindtext

\begin{align*}
    & (f,f)_{[x^3]_{1}} = (f,f)_{[x^3]_{1}}=0 \\ 
    & (f,g)_{[x^3]_{1}} = (f,g)_{[x^3]_{3}}=0 \\
    \noalign{\hspace{-\parindent}$(f,h)_{[xxy]_{1}} = (f,h)_{[xxy]_{3}}=0$}
    \noalign{\hspace{-\parindent}$(f,p)_{[xxy]_{1}} = (f,p)_{[xxy]_{3}}=0$}
    & (f,m)_{[xxt]_{1}} = [xx]_{1} \dashv t  - x \dashv ([xt]_{1} - [tx]_{2}) = [xtx]_{1}\\
    & (f,m)_{[xxt]_{3}} = [xx]_{1}\vdash t - x \vdash ([xt]_{1} - [tx]_{2})=[xxt]_3-[xxt]_2+[xtx]_3\\
    & (g,f)_{[x^3]_{1}} =(g,f)_{[x^3]_{3}}=0\\
\end{align*}

\end{document}

And the output is: enter image description here

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .